Advocate Immunity Is Active When Integrity In The Exercise Of The Profession - Jamillah Jamillah; Maswandi Maswandi (Universitas Dharmawangsa, 2023)
n the practice of law enforcement, many advocates who abuse the right of immunity of this profession and similarly in contrast, many other law enforcers do not understand the rightof Advocate immunity. This right of immunity will be strong if an advocate carries out hisprofession in line with his integrity. The results concluded that the application of the rightof immunity is successful if between law enforcement agencies work in accordance with thedignity of the law and each legal actor maintains professionalism according to the code ofethics and adheres to the principle of good faith to uphold the law and justice to benefit thewider community and the right of immunityKeywords: Immunity, Law, Integrity